Web-Based Internship Information System Using Geolocation and Geofencing in the Information Systems Department of Muria Kudus University - Auliya Firdausiyah; Fajar Nugraha; Supriyono Supriyono (JUSIFO : Jurnal Sistem Informasi, 2026)
Internship administration at Universitas Muria Kudus remains constrained by manual attendance records, physical logbooks, limited progress monitoring, and the absence of location-based validation. This study developed and evaluated a web-based internship information system integrating geolocation and geofencing to support attendance control and multi-actor academic workflows. The system was implemented using the PHP Laravel framework and MySQL database following the Waterfall model. Its core functions include geofencing-based check-in, digital logbook submission and verification, early warning monitoring, partner classification, assessment, and administrative reporting. Functional validation showed that the geofencing module produced the expected responses for locations inside, on, and outside the configured boundary, as well as when location access was unavailable or inaccurate. Black Box Testing confirmed that all six tested functions operated according to their specified requirements. Performance testing across five trials per process produced mean response times ranging from 1.76 to 3.14 seconds. The system provides an integrated foundation for structured, location-aware internship management in higher education.